The Virtual Dimension of Legal System - Gubaydullin, Aydar; Shigabutdinova, Alina (Journal of History Culture and Art Research, 2018)
The purpose of the present research is identification of existence of legal system in virtual space. This purpose is concretized by the following tasks: the analysis of existence of positive law, legal science, legal consciousness in digital measurement; disclosure of some features of law-making on the Internet; identification of separate aspects of right realization in virtual space. The methodological device of this research is based on dialectic understanding of surrounding life in which borders between real and virtual space have flexible character. At the same time use of the system approach causing existence of various methods of scientific knowledge is inevitable. It is possible to distinguish from them structurally functional, legalistic, and comparative and other methods. Authors of article recognize the known pluralism of the used categories. However in this research the terms "virtual space", "digital space", "Internet space", "cyberspace" are used as synonyms. Results of the research can find the application in the sphere of jurisprudence and legal education. Also they can be considered in law-making processes.